Essential thrombocythaemia with mutation in MPL: clinicopathological correlation and comparison with JAK2V617F-mutated and CALR-mutated genotypes. Issue 11 (22nd June 2018) - Alvarez-Larran, Alberto; Martínez, Daniel; Arenillas, Leonor; Rubio, Ariadna; Arellano-Rodrigo, Eduardo; Hernández Boluda, Juan Carlos; Papaleo, Natalia; Caballero, Gonzalo; Martínez, Clara; Ferrer-Marín, Francisca; Mata, María Isabel; Pérez-Encinas, Manuel; et al.
Abstract : Aim: To characterise the clinical and histological features of MPL -mutated essential thrombocythaemia (ET). Patients and methods: Bone marrow biopsies of 175 patients with ET were centrally reviewed according to the 2016 WHO classification, including 42 cases with MPL mutation, 98 JAK2 V617F-mutated and 35 CALR -mutated. Clinical and histological features were compared among the three genotypes included in the current 2016 WHO classification and among the different types of MPL mutations. Results: Patients with MPL -mutated ET were significantly older than those with the other genotypes. Haematological values at diagnosis were similar among MPL -mutated and CALR -mutated ET, with both genotypes showing higher platelet counts and lower haemoglobin values than ET with JAK2 V617F genotype. In the bone marrow, the median number of megakaryocytes was higher in MPL and CALR than in JAK2 V617F genotype (16, 19 and 14 megakaryocytes per ×20 power field, respectively, p=0.004). Histological features of prefibrotic myelofibrosis were rarely observed in MPL genotype, whereas sinusoidal hyperplasia, dense clusters of megakaryocytes and reticulin fibrosis were more frequent in CALR -mutated ET, with 11% of such cases fulfilling WHO 2016 histological criteria of prefibrotic myelofibrosis. With a median follow-up of 3.5 years, no significant differences were seen among genotypes regarding survival, vascular complications or myelofibrotic transformation. There were no significant differences in the clinical data or in the histological characteristics depending on the type of MPL mutation. Conclusion: MPL and CALR ET genotypes share clinical and histological characteristics. In contrast to CALR genotype, features of prefibrotic myelofibrosis are uncommon in MPL -mutated ET.